Fairness-Aware Utility Maximization for Multi-UAV-Aided Terrestrial Networks - Nishant Gupta; Satyam Agarwal; Aymen Fakhreddine (IEEE Open Journal of Vehicular Technology)
Integrating unmanned aerial vehicles (UAVs) with terrestrial networks can enable high-speed communication in various applications. UAVs can serve as aerial base stations (ABSs), offering several benefits to the existing terrestrial networks, such as enhanced coverage, increased capacity, rapid deployment, and mobile communication support. However, this integration presents various technical challenges, including coordination, interference management, and dynamic allocation of resources. To address these key challenges, in this paper, we maximize the network utility by jointly optimizing the scheduling and cell association, transmit power of all base stations, and ABS deployment locations in the presence of co-channel interference. A two-stage approach is proposed to obtain a solution. In the first stage, we propose a heuristic solution by using the clustering algorithm to determine the initial ABS locations and user scheduling while ignoring the co-channel interference. In the second stage, we utilize the solution obtained in the first part and develop an interference-aware iterative scheme to jointly optimize user scheduling, resource allocation, and ABS placement. Given the non-convex nature of this problem, we employ the successive convex approximation technique to approximate the non-convex objectives and constraints. Numerical results show the proposed approach's insights and effectiveness over other schemes. Specifically, our proposed approach provides an average of 25% improvement over the benchmark schemes.